Umblical cord blood pH, blood gases, creatin posphokinase and MB isoenzyme analyses in preterm infants of ritodrine administered 24-34 weeks pregnant women as an indicator of perinatal asphyxia (Annals of Medical Research, 2021)
None
Keywords: s : Ritodrine, preterm labor, fetal distress